PHYTOCONSTITUENTS FROM RICHARDIA SCABRA L. AND ITS BIOLOGICAL ACTIVITIES - KATHIRVEL POONKODI (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The present chemical investigation is carried out for the isolation of active phytoconstituents from Richardia scabra Linn belongs to Rubiaceae family. Methods: Â Air dried plant material was macerated with petroleum ether and defatted plant was introduced in Soxhlet apparatus with methanol. Both extracts were subjected to column chromatography for isolation of active chemicals. Result: Two novel coumarins from the methanol extract and one fatty acid from the petroleum ether extract were isolated from Richardia. Oleic acid, heraclenin and isopsoralen were isolated for the Â first time in the genus Richardia. Furthermore, the cytotoxicity of the heraclenin was evaluated with HeLa cell line and cell cycle arrest by Fluorescent assisted cell sorting analysis. Conclusion: The result revealed that the heraclenin has potent cytotoxicity with the IC50 value was 46.09Âµg/ml and it induced cell cycle arrest in G0/G1 phase about (51.2%), S phase (30.2) and resulted in a decline in the percentage of G2-M phase. Keywords: cell cycle, cytotoxicity, Heraclenin, isopsoralen, Oleic acid,Â Â Richardia scabra Â